Synergistic effect of ammonium and potassium on carrot growth, physio-biochemical mechanisms, and water use efficiency under varying irrigation regimes - Ayman M. S. Elshamly; Ahmed D. S. Abaza; Abd El-Zaher M. A. Mustafa; Humaira Rizwana; Javed Iqbal; Shabir Ahmad; Rashid Iqbal; Nazim S. Gruda (Scientific Reports)
Abstract The beneficial effects of ammonium nitrate and potassium humate on carrots are well-documented. However, their impact on physiological and biochemical mechanisms under varying irrigation conditions still needs to be explored. Here, we investigated the effects of soil-applied ammonium nitrate and foliar-applied potassium humate on the physio-chemical characteristics and water use efficiency of carrot plants under three irrigation levels: 100%, 80%, and 60% of crop evapotranspiration (ETc). Carrot plants were treated with two rates of soil ammonium nitrate (200 and 250 kg N ha− 1), foliar potassium humate (200 and 400 g 100 L− 1), and four combinations of these treatments. Under 80% of ETc, the combined applications of soil ammonium nitrate and foliar potassium humate significantly influenced the leaf contents of chlorophyll a, nitrate, ammonium, catalase, carbohydrate, and soluble sugar patterns, enhancing osmotic regulation under water deficit conditions. Interestingly, when carrots were irrigated by 100% of ETc instead of 80 and 60% and sprayed with 400 g 100 L− 1 of potassium humate in combination with 250 kg N ha− 1 of ammonium nitrate, water use was decreased by 49.2 and 30.7%, respectively. We attributed that to: a), the observed increments in NH4 concentrations in the leaves under 100% ETc which caused negative physiological impacts on chlorophyll, and b) the change in C/N and N/P ratios. This highlights the importance of choosing a suitable irrigation pattern for carrot crops when the potassium humate in combination with ammonium nitrate is adapted. Overall, using foliar potassium humate at a rate of 200 g 100 L− 1 with soil ammonium nitrate applications at 250 kg N ha− 1 under 80% ETc attained the highest yield and water use efficiency.